The Insertion of a Subacromial Balloon Spacer Can Provide Symptom Relief and Functional Improvement at a Minimum 5-Year Follow-Up in Patients With Massive Irreparable Rotator Cuff Tears - Mohamad Y. Fares, M.D., M.Sc; Jonathan Koa, B.Sc; Jaspal Singh, M.D; Joseph A. Abboud, M.D (Elsevier, 2024)
Purpose: To examine long-term patient-reported outcomes and range of motion in patients with massive irreparable rotator cuff tears (MIRCTs) who underwent subacromial balloon spacer implantation. Methods: A retrospective review of all patients who underwent subacromial balloon placement procedure for MIRCTs at our institution was conducted. Patients with adequate preoperative and postoperative data, with at least 5 years of follow-up, were included in our study. Outcome measures were range of motion (forward elevation), American Shoulder and Elbow Surgeon (ASES) score, and visual analog scale (VAS) score. Independent t test was conducted to check for statistically significant differences between preoperative and postoperative outcome scores, with P < .05 deemed significant. Results: Ten patients were identified: 4 were lost to follow-up beyond 2 years and were excluded. One was converted to an arthroplasty at the 1-year mark and was then lost to follow-up (conversion rate: 16.6%). Five patients had at least 5 years of follow-up after the balloon procedure and were involved in our case series analysis. Mean age was 63.1 years, and mean follow-up was 5.8 years (range, 5-7 years). Preoperatively, mean forward elevation was 110 degrees, mean ASES score was 40.68, and mean VAS score was 6.2. On follow-up, mean forward elevation was 163 degrees (P = .007), mean ASES score was 90.97 (P = .001), and mean VAS score was 0.9 (P = .004). All patients showed significant improvements in all outcome measures, and none had any significant complications. Conclusions: In this study, we found that the use of a subacromial balloon spacer can lead to good outcomes at a minimum 5-year follow-up in patients with MIRCTs. Level of Evidence: Level IV, therapeutic case series.